From the time-ordered data to the Maximum-Likelihood temperature maps of the Cosmic Microwave Backgorund anisotropy - Stompor, R; Balbi, A; Borrill, J; Ferreira, P; Hanany, S; Jaffe, A; Lee, A; Oh, S; Rabii, B; Richards, P; Smoot, G; Winant, C; et al. (2000)
We review selected methods of the Cosmic Microwave Background data analysis appropriate for the analysis of the largest currently available data sets. We focus on techniques of the time-ordered data manipulation and map making algorithms based on the maximum-likelihood approach. The presented methods have been applied to the MAXIMA data analysis (Hanany et al 2000) and the description of the algorithms is illustrated with the examples drawn from that experience. The more extensive presentation of the here-mentioned issues will be given in the forthcoming paper (Stompor et al 2001).